Analisis Preferensi Konsumen Daging Ayam Broiler di Pasar Tradisional Kabupaten Jember Jawa Timur - Zahro, Sofika Rohmatuz (Universitas Galuh, 2024)
Broiler chicken meat or usually known as broiler chicken, is easy to find in traditional markets and modern markets in Jember Regency. Consumers see a product as a collection of attributes that will determine a preference. A person's preferences can be formed through a person's behavior patterns which are based on several reasons, namely, previous experience and hereditary beliefs. The existence of people who still choose traditional markets amidst the rise of modern markets has become a social phenomenon. The aim of the research is to find out what attributes of broiler chicken meat are consumer preferences and what attributes are most considered by consumers. The research method used is descriptive. The data collection methods in this research are primary and secondary data. The analytical methods used are Chi Square analysis and Fishbein Multiattribute analysis. The results of the research show that all the attributes observed in this study, namely meat color, meat aroma, meat parts and cut shape, are significantly different within the 95% confidence level, meaning that there are differences in consumer preferences for the existing attributes (color, aroma, part and shape of the cut). on broiler chicken meat. Broiler chicken meat which is the consumer preference in traditional markets in Jember Regency is broiler chicken meat with attributes of choice including yellowish white color, non-fishy aroma, chicken thigh meat, and even cut shape. The attributes that are most considered and those that are least considered are color, aroma, part of the meat, shape of cut.